Antileukemic activity and cellular effects of rhodium(III) crown thiaether complexes - Bieda, Ruth; Kitanovic, Igor; Alborzinia, Hamed; Meyer, Andreas; Ott, Ingo; Wölfl, Stefan; Sheldrick, William S. (BioMetals, 2011)
The cytostatic properties of novel rhodium(III) thiacrown ether complexes [RhCl(LL)([9]aneS3)]n+ with either aromatic κ2N ligands (n = 2) or anionic chelate ligands (n = 1) have been investigated for the human cancer cell lines HT-29 and MCF-7 and for immortalized HEK-293 cells. Taken together with literature IC50 values for analogous complexes with polypyridyl ligands or 1,4-dithiane, the in vitro assays indicate that dicationic complexes with soft κ2N (imino) or κ2S (thiaether) ligands exhibit significantly higher antiproliferative effects than those with hard κ2N (amino) ligands. Dicationic complexes are more active than monocationic complexes with similar ligands. Pronounced apoptosis-inducing properties towards Jurkat cells were established for complexes with LL = bpm, dpq, and 1,4-dithiane. The order of activity (bpm > 1,4-dithiane > dpq > bpy) contrasts to that observed for adhesive cancer cells (bpm > bpy, 1,4-dithiane > dpq). Necrosis is insignificant in all cases. The percentage of Jurkat cells exhibiting apoptosis after 24 or 48 h incubation periods is directly correlated to the percentage of cells exhibiting high levels of reactive oxygen species. As established by online monitoring with a sensor chip system, treatment of MCF-7 cells with the bpm and 1,4-dithiane complexes leads to a significant and permanent concentration-dependent decrease in oxygen consumption and cellular adhesion.
Gesehen am 23.03.2022